Essays on human capital and taxation - Collins, Kirk A (University of Ottawa (Canada), 2004)
This body of work contains four essays. The first three use a novel approach to measuring the impact that taxation has on individuals' incentive to invest in human capital; specifically, a university education. The final essay uses the results from the first three to explore the capital levy problem in a new light. Using the framework for effective marginal tax rates (EMTRs) on physical capital, a conceptual framework is developed for measuring similar rates on human capital. Unlike their physical capital counterpart, effective tax rates (ETRs) on human capital are not measured at the margin, but rather are based on the next level of education attainment (e.g. high school vs. university/college). The reason, which is explained in detail, is that the lumpiness of human capital investment matters, unlike for physical capital. Results show that the progressivity of personal income taxation plays a large role in human capital ETRs, as do non-tax policy instruments (e.g. registered education savings plans, tuition and other direct costs to education, education allowances, etc.). Human capital ETRs are nonuniform, like their EMTR cousins, but are lower in magnitude. The results also support the view that the tax structure may influence the incentive for highly educated Canadians to seek employment in the United States, mitigating the brain drain phenomenon. The final essay looks at the capital levy problem. If capital investments are irreversible, governments can tax these items ex post with little (or no) deadweight loss. As a result, smart investors end up investing less in certain types of capital. In the end there is an underinvestment in capital. The problem with this view is that it only describes what happens in the case of physical capital investment. Given the importance of human capital in today's "knowledge-based" economy, it is imperative that the framework address both of these types of capital. A general equilibrium model is developed. Results support the view that it is more than wages alone that determine migration incentives; the structure of the tax system, public goods, adjustment costs, are all shown to play a role. Simulation results are also provided.
Keywords: Economics, Labor.